Topographical Evaluation of Neovessels in Proliferative Diabetic Retinopathy by Using a Multimodal Imaging Approach - Eliana Costanzo; Vito Fenicia; Sara Giammaria; Maria Sole Polito; Giulia Mecarelli; Monica Varano; Mariacristina Parravano (Journal of Clinical Medicine, 2026)
Background: To evaluate structural and microvascular parameters in proliferative diabetic retinopathy (PDR) eyes, based on topographical location of neovessels (NVs). Methods: Retrospective cross-sectional study including PDR eyes without clinically significant macular edema. Patients were stratified on NVs location: disc (NVD), elsewhere (NVE), both (NVD + NVE). Optical coherence tomography (OCT) and OCT-angiography (OCTA) were performed to measure central macular thickness (CMT), choroidal thickness (ChT), retinal layer thicknesses, foveal avascular zone (FAZ) area, retinal perfusion density (PD) and choriocapillaris flow deficit (CC FD%). Results: Twenty-six PDR eyes from 26 patients (20 males, mean age 53.3 ± 14.2 years) were analyzed, 6 with NVD, 14 with NVE and 6 with NVD + NVE, respectively. No significant differences in CMT, ChT, PD and CC FD% between groups were found. OCT layer-by-layer analysis showed lower inner retinal layer thicknesses in NVE group. FAZ area was larger in NVD (p = 0.05). In presence of NVD, the regression analysis between FAZ and OCTA metrics showed a negative linear relationship with PD, and a positive relationship with CC FD%. Conclusions: In NVD group, a thickening of inner retinal layers and FAZ enlargement were found. These results support the hypothesis of a more pronounced ischemic damage in PDR eyes with NVs at the optic disc.